GEOPHYSICAL CHARACTERISTICS OF THE BOSUMTWI IMPACT CRATER FROM SEISMIC, GRAVITY AND MAGNETIC MEASUREMENTS - S. K. Danuor; A. A. Aning; J. Pohl; T. Karp; H. Berckhemer (European Scientific Journal, ESJ, 2013)
﻿Geophysical investigations have been carried out at the Bosumtwi impact crater in Ghana to determine the geophysical characteristics that are related to the impact process. Gravity, magnetic and wide angle seismic reflection and refraction studies have been used to obtain information on the impact-related anomalies. Seismic modelling gave a three layer model of the crater consisting of the water layer with a velocity of 1.45 km/s, post-impact sediments with low velocities of 1.50 - 1.65 km/s and a third layer which is referred to as the crater floor made up of basement rocks. Seismic velocities were found to increase from 2.8 km/s at the interface of post-impact sediments and crater floor to about 5 km/s in 1.6 km depth. The central uplift, which confirms the Bosumtwi crater as a complex impact crater, was found to be 250 m below the water surface. The velocity of 2.8 km/s is interpreted to be due to fallback breccia which completely covered the central uplift. Gravity measurements yielded a maximum negative anomaly of 18 mgal over the crater. This is interpreted to be caused by fractured and brecciated rocks in the rim area and below the crater floor, breccias within the crater, and sedimentary and water infilling of the lake. Magnetic modelling showed that the magnetized bodies are found to be located between 250 and 610 m depths below the lake. The magnetized bodies have been interpreted to be thin sheets of possibly suevitic impact formations or melt bodies adjacent to the central uplift.